An unusual presentation of giant sebaceous cyst over the back: A case report - Neel Doshi; Pratik Gond; Tanisha Prasad; Abhigan Babu Shrestha (Clinical Case Reports, 2024)
Key Clinical Message Sebaceous cysts are a prevalent form of benign cutaneous cysts that often manifest as epidermal cysts when their size exceeds 5 cm in diameter. Despite their infrequent occurrence, cases of massive epidermal cysts measuring 5 cm or larger have been documented. Malignant transformations within epidermal cysts are exceedingly rare but not impossible. Although their development into malignancies is a rare event, it is essential to acknowledge the potential for benign epidermal cysts to undergo such transformation. In clinical terminology, these cysts predominantly affect the facial, cervical, and dorsal regions. They usually remain asymptomatic, with their formation attributed to the sequestration of epithelial remnants during embryonic fusion or trauma. In this report, we present a remarkable case of a colossal epidermal cyst found on the upper back of a 75‐year‐old male individual, highlighting the uncommon nature of such occurrences within the medical domain. This case adds to the literature by presenting a rare case report highlighting the clinical presentation, probable consequences, and surgical therapy of larger epidermal cysts.